2015
DOI: 10.5487/tr.2015.31.3.221
|View full text |Cite
|
Sign up to set email alerts
|

Total Diet Studies as a Tool for Ensuring Food Safety

Abstract: With the diversification and internationalization of the food industry and the increased focus on health from a majority of consumers, food safety policies are being implemented based on scientific evidence. Risk analysis represents the most useful scientific approach for making food safety decisions. Total diet study (TDS) is often used as a risk assessment tool to evaluate exposure to hazardous elements. Many countries perform TDSs to screen for chemicals in foods and analyze exposure trends to hazardous ele… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 15 publications
0
10
0
Order By: Relevance
“…19 There are two obvious advantages of a TDS: (1) the composite samples used in a TDS are aggregates of many subsamples collected on a large scale, which is a cost-effective and suitable method for the complex analysis of chemicals; and (2) the chemicals analyzed in a TDS are in a consumable form because they are extracted from cooked food. 20 For analytically complex compounds such as CPs, a TDS is an efficient tool to monitor human dietary exposure nationwide. Iino et al 21 found that fat samples from the first Japanese market basket study had the highest SCCP concentrations, followed by shellfish and fish samples.…”
Section: ■ Introductionmentioning
confidence: 99%
“…19 There are two obvious advantages of a TDS: (1) the composite samples used in a TDS are aggregates of many subsamples collected on a large scale, which is a cost-effective and suitable method for the complex analysis of chemicals; and (2) the chemicals analyzed in a TDS are in a consumable form because they are extracted from cooked food. 20 For analytically complex compounds such as CPs, a TDS is an efficient tool to monitor human dietary exposure nationwide. Iino et al 21 found that fat samples from the first Japanese market basket study had the highest SCCP concentrations, followed by shellfish and fish samples.…”
Section: ■ Introductionmentioning
confidence: 99%
“…Risk analysis has been recommended as one of the most effective measurements for managing food safety against globalized food scams and scandals. A risk analysis comprising three components, namely, risk assessment, risk management, and risk communication, is used to respond to food accidents and develop safety standards (Lee et al 2015 ). Figure 3 shows the paradigm of risk analysis and its comprising factors (B.M.J.…”
Section: Effects Of Codex On Korean Food Safety Management Systemsmentioning
confidence: 99%
“…From the studies presented in Table 2, Sirot et al (2013) and Sprong et al (2016a) evaluated the exposure of French and Dutch populations, respectively, to mycotoxins.. According to Lee et al (2015), countries as Australia, France, Korea and China had developed their country-specific TDSs including mycotoxins but all countries are encouraged to conduct total diet studies to assess the safety and nutritional quality of diet of their population since TDS is not only a costeffective tool but also a realistic tool for risk assessment of chemicals in foods. Actually, the TDS EXPOSURE project aims to provide guidance for future TDSs, as well as for new TDSs in countries that have no TDS experience (http:// tds-exposure.eu/).…”
Section: Worldwide Exposure Assessment Of Co-occurring Mycotoxins In mentioning
confidence: 99%